PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV PADA MATERI KELILING DAN LUAS BANGUN DATAR - Enjelina Adriwati; Wara Sabon Dominikus; Adam Bol Nifu Benu (Journal of Character and ELementary Education, 2023)
This study aims to determine the effect of the Realistic Mathematics Education (PMR) approach on the mathematics learning outcomes of fourth-grade students on the circumference and area of ​​flat shapes. The research method used is quantitative with a Pre-Experimental Design approach of the One-Group Pretest-Posttest Design type. The sampling technique used a simple random sampling technique. Data on student learning outcomes were collected using a multiple-choice test instrument consisting of 20 questions. This study was analyzed using prerequisite tests in the form of normality and homogeneity tests and hypothesis testing using paired sample t-tests. The results showed that there was a significant influence in the use of the Realistic Mathematics Education approach to the mathematics learning outcomes of fourth-grade students on the circumference and area of ​​flat shapes. This is evidenced by the results of the paired sample t-test with a significance level of 0.05 and a sig. (2-tailed) value of 0.000 <0.05, which means that H₀ is rejected and Hₐ is accepted.